Hubungan Fungsi Keluarga Dengan Pemilihan Alat Kontrasepsi IUD Dan Non IUD Pada Akseptor KB - Sitta, Alfi Nurmas; , dr. Anika Candrasari, M.Kes; , dr. Mohammad Shoim Dasuki, M. Kes (2015)
Background: The public comprehension that Family Planning (KB) is only women's problem, it indicated less healthy family functioning. Syringe contraceptives is more public interest than IUD (Intra Uterine Device) which have high effectiveness. Selection of contraception is a health's problem that can be influenced by family function. Purpose: The purpose of this research is analyze relationship of family function with selection of contraceptives IUD and Non IUD to the acceptor KB. Method: This research is an analytic observational with cross sectional approachment. It was performed on acceptor KB at Maternity Hospitals and Pusdiklat Migas Cepu Clinic on January 5th-31th 2015. The amount sample was used in 49 samples with simple random sampling. The data was collected by questionnaire and medical record. Data analysis was using with chi-square. Result: The respondents who have healthy family function chose IUD in 10 respondents (20,41%) and Non IUD's 16 respondents (32,65%), less healthy family function chose IUD in 10 respondents (20,41%) and Non IUD's 16 respondents (12,24%), unhealthy family function chose IUD in 6 respondents (12,24%) and Non IUD's 6 respondents (12,24%). Result of statistic chi-square = 8.597 and p value= 0.014. Conclusion: There is a relationship of family function with selection of contraceptives IUD and Non IUD to the acceptor KB